Current validity of Wilhelm Wundt’s position on the body-mind problem - Freitas-Araujo, Saulo de (2007)
The body-mind problem has been a central and permanent problem not only in the history of psychology but in all the sciences that deal with so-called mental processes. With progress in the neurosciences in the past decades, there is a contemporary trend towards the solution of the problem through brain research. The aim of this study is demonstrate that: (a) the current trend shows a form of naïve materialism, similar to 19th century, “naïve materialism”; and (b) Wilhelm Wundt’s antimaterialist position offers an alternative to naïve materialism which shows to be more plausible.